TRANSFORMASI DIGITAL DAN PENGARUHNYA TERHADAP PERILAKU MAHASISWA DALAM MENGGUNAKAN SISTEM INFORMASI DI UNIVERSITAS SALAKANAGARA BANTEN - Slamet, Tri Setyo; Rini, Puput Puspito (Jurnal Ilmiah Sistem Informasi, 2024)
Digital transformation in the world of education has changed the way students interact with academic information systems. Universitas Salakanagara Banten has implemented a digital academic information system to improve the efficiency of educational services. This change has an impact on student behavior in accessing and using the system, especially in the aspects of digital literacy, ease of use, and personal data security. This study aims to analyze the influence of digital transformation on student behavior in using academic information systems. This study highlights the factors that affect the level of system adoption, student satisfaction, and obstacles faced in the use of digital-based academic systems. The research method used is a quantitative approach with the distribution of questionnaires to students of Salakanagara University Banten. Descriptive and inferential statistical analysis was used to identify the pattern of relationship between digital literacy, ease of use, and data security factors on the intensity of use of academic information systems. The results of the study show that students with a higher level of digital literacy tend to be more active in using academic information systems. The ease of use factor contributes significantly to user satisfaction, while concerns related to data security are one of the main barriers to system adoption. The conclusion of this study confirms that digital transformation in the academic environment requires a more inclusive strategy, especially in improving students' digital literacy and ensuring the security of information systems. Recommendations are given to improve the accessibility of the system and provide more comprehensive training for students in the use of digital academic technology